COVID-19, Family Stress and Domestic Violence: Remote Work, Isolation and Bargaining Power - Louis-Philippe Béland; Abel Brodeur; Joanne Haddad; Derek Mikola (Institute of Labor Economics (IZA), 2020)
We investigate the impacts of COVID-19 on domestic violence and family stress. Our empirical analysis relies on a unique online survey, Canadian Perspective Survey Series, that allow us to disentangle the mechanisms through which COVID-19 may affect family stress and domestic violence. We find no evidence that employment status and work arrangements are related to higher self-reported levels of family stress and violence in the home due to confinement, suggesting that remote working on a large scale does not lead to family violence. In contrast, we find that the inability to meet financial obligations and maintaining social ties significantly increase reported family stress and domestic violence. These findings are consistent with two alternative mechanisms: social isolation and decreased bargaining power for women. Last, we provide suggestive evidence that receiving financial relief does not mitigate the effect of financial worries on domestic violence and family stress. We conclude that targeted programs supporting victims of domestic violence may be more effective.
Keywords: D03; I18; J12; 330; COVID-19; lockdown; domestic violence; family stress; isolation and remote work